Power in the Global Refugee Regime: Understanding Expressions and Experiences of Power in Global and Local Contexts - Milner, James; Wojnarowicz, Krystyna (Refuge: Canada’s Journal on Refugees, 2017)
Since the late 1980s, scholars have highlighted the role of diverse conceptualizations of power in explaining the functioning of the global refugee regime. Part of this literature has examined the functioning of power in global contexts, while another part has explored expressions and experiences of power in local contexts. While these approaches illustrate how power may be expressed and experienced in the diverse contexts of the regime, can we conceptualize power in a way that engages with the functioning of the refugee regime in both global and local contexts? Can a more disaggregated understanding of power, sensitive to form and context of expression, open new areas of enquiry into the functioning of the regime and help explain its ability and inability to fulfill its core mandate of protection and solutions for refugees? In response, this article draws on the literature on power in global governance to propose a heuristic framework for understanding power and influence in the diverse context of the global refugee regime. It argues that various forms of power co-exist within the regime, and that further research could usefully examine the manifestations and implications of these forms of power through the making and implementation of global refugee policy.